Adaptive Reproductive Strategies in Schizothoracine Fishes: Dual Spawning Phases and Environmental Synchronization in Himalayan Ecosystems - Syed Talia Mushtaq (Aquaculture, Fish and Fisheries)
ABSTRACT Schizothoracine fishes, endemic to the Himalayan region, exhibit remarkable adaptive reproductive strategies in response to their challenging high‐altitude aquatic environments. This review synthesizes current knowledge on the dual spawning phases and environmental synchronization observed in these species, with a focus on the genus Schizothorax. These fishes demonstrate a unique ability to spawn twice annually, with distinct breeding periods in summer (June–October) and winter (January–March). Dual spawning phases allow Schizothoracine fishes to optimize reproductive output by synchronizing hatching and larval emergence with periods of high food availability and favourable temperatures, thereby increasing offspring survival (Bromage et al. 1993; Tao et al. 2018). This reproductive plasticity is closely synchronized with environmental cues such as water temperature, discharge, and photoperiod, allowing for optimized breeding cycles in dynamic ecosystems. Notably, spawning periods may vary among populations of the same species based on local ecological conditions and elevational gradients. The review explores the adaptive significance of these strategies, including increased reproductive success and enhanced population resilience. In addition, it examines the implications of these adaptations for conservation efforts in the face of climate change and anthropogenic pressures in the Himalayan region.